The Ethics of Teaching at Sites of Violence and Trauma Student Encounters with the Holocaust - Bormann, Natalie (Palgrave Macmillan US, 2018)
This book chronicles a professor's experience with a group of US undergraduate students at Holocaust memorials, museums, and sites of remembrance as part of a yearly Holocaust study abroad program to Germany and Poland. Narrated through a series of personal encounters, The Ethics of Teaching at Sites of Violence and Trauma synthesizes a concrete experiential teaching account - on issues ranging from trauma tourism to the ethics of spectatorship - with contemporary debates on Holocaust education. In doing so, this book seeks to offer a critical assessment on the possibilities and limitations of teaching at sites that were central to the planning and execution of the Holocaust. .